The relationship between anesthesia and melatonin: a review - Guo, Rui; Ye, Junming; Liao, Baozhen; Luo, Xin; Rao, Panguo (Frontiers in Pharmacology, 2023)
Introduction: This comprehensive review delves into the intricate and multifaceted relationship between anesthesia and melatonin, aiming to provide essential insights for perioperative clinical anesthesiologists and stimulate interest in related research. Anesthesia and surgery have the potential to disrupt melatonin secretion, leading to sleep disorders, postoperative neurocognitive dysfunction and other symptoms. In comparison to previous reviews, this review provides a comprehensive summary of the various aspects linking melatonin and anesthesia, going beyond isolated perspectives. It explores the potential benefits of administering melatonin during the perioperative period, including alleviating anxiety, reducing pain, enhancing perioperative sleep quality, as well as demonstrating immunomodulatory and anti-tumor effects, potentially offering significant advantages for cancer surgery patients. Recent Findings: Anesthesia and surgery have a significant impact on melatonin secretion, the hormone crucial for maintaining circadian rhythms. These procedures disrupt the normal secretion of melatonin, leading to various adverse effects such as sleep disturbances, pain, and postoperative neurocognitive dysfunction. However, the administration of exogenous melatonin during the perioperative period has yielded promising results. It has been observed that perioperative melatonin supplementation can effectively reduce anxiety levels, improve pain management, enhance the quality of perioperative sleep, and potentially decrease the occurrence of postoperative delirium. In recent years, studies have found that melatonin has the potential to improve immune function and exhibit anti-cancer effects, further underscoring its potential advantages for patients undergoing cancer surgery. Summary: In summary, melatonin can serve as an adjuvant drug for anesthesia during the perioperative period. Its administration has demonstrated numerous positive effects, including anti-anxiety properties, sedation, analgesia, improved postoperative sleep, and the potential to reduce the incidence of postoperative delirium. Furthermore, its immune-modulating and anti-tumor effects make it particularly valuable for cancer surgery patients. However, further studies are required to determine the optimal dosage, long-term safety, and potential adverse reactions associated with melatonin administration.